Reform from Within: Efforts by Kadhis' Courts in Kenya to Empower Muslim Women's Access to Matrimonial Property and Divorce Settlements Rights - Hashim, Abdulkadir (KnE Social Sciences, 2024)
When the relationship ends through divorce or separation, Muslim married women risk losing their share of the matrimonial property and other marital rights after divorce. As a result, Muslim widowed women lose the rights to ownership, control, and access to properties they enjoyed during their marriage life. The application of Muslim personal law (MPL) in the Kadhis’ courts in Kenya, similar to other jurisdictions, is highly dependent on social customs that to a great extent hinders women’s access to their rights after divorce. Previously, Muslim women appearing before the Kadhis’ courts in Kenya would persevere their marital sufferings and submit to patriarchal norms of male priority, authority, and power. Current religious underpinnings of MPL in the Kadhis’ courts in Kenya demonstrate a continuing change in Muslim religious courts toward expanding Muslim women’s access to justice. Neo-Kadhis are influenced by contemporary Muslim legal opinions and conventional legal trends and constitutional instruments such as the Constitution of Kenya 2010 that provides for gender equality, including equality in ownership of property, and prohibits the state from making laws that arbitrarily deprive a person of property or the enjoyment of the rights/interests over property on any discriminatory grounds. The Neo-kadhis are pioneering the reform process that adopts a progressive approach in responding to emerging legal issues related to women litigants’ rights to matrimonial property rights and divorce settlements rights in the form of Mata’a (consolatory gift) as opposed to the prevalent Islamic traditional approach in Muslim religious courts. Influenced by conventional court decisions, recent cases decided by the Neo-Kadhis in Kenya consider wives’ day-to-day household activities and monetary contributions in assessing matrimonial property rights after divorce. This paper examines the dynamics of the progressive approach adopted by the Neo-Kadhis in Kenya toward enhancing women’s access to justice rights and gender relations in Muslim religious courts in Kenya and beyond. Keywords: Access to matrimonial rights, divorce settlement rights, Kadhi’s courts, Muslim women, Islamic family law, Ken